Assessing Antibiotic Stewardship Knowledge Among Healthcare Professionals in an Indonesian Teaching Hospital - Taufiqurohman, Taufiqurohman; Tanjung, Rahmadiyah S.; Amalia, Khoirunnisa (Academic Hospital Journal, 2025)
Background: Hospitals all around Indonesia have adopted antimicrobial stewardship. Hospitals were encouraged to adopt the program through required AMS programs as part of hospital accreditation and the implementation of a national policy. Pharmacists actively contribute to the program's implementation, which has a significant impact on hospitals. Additionally, the involvement of other healthcare professionals is crucial for the program's success.Method: The study was conducted at UGM Academic Hospital from June 1 to October 31, 2024. This study design is non-experimental research with an analytical cross-sectional approach, and data collection was conducted prospectively using questionnaires. Respondents are specialist, general practitioners, dentists, pharmacists, and nurses working at UGM Academic Hospital, possess a valid practice license, and are willing to participate as respondents in the study.Result:  The questionnaire was collected from healthcare professionals at UGM Academic Hospital. 91 participants, representatives from three professional groups: nurses/midwives (49.5%), physicians (36.3%), and pharmacists 14.3%). High knowledge scores (reaching the maximum score) on antimicrobial stewardship were achieved by 69.2% (63/91) of the respondents. Compared to nurses/midwives and physicians, pharmacists had a greater mean level of antibiotic stewardship knowledge.Conclusion: Healthcare professionals demonstrated good knowledge of antimicrobial stewardship; however, a few healthcare workers still scored low. A regular training program must be carried out to enhance the antimicrobial stewardship program in the hospital.